2006
DOI: 10.1017/s1462399406000068
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolism in the central nervous system: medical implications

Abstract: The metabolism of the amino acid L-tryptophan is a highly regulated physiological process leading to the generation of several neuroactive compounds within the central nervous system. These include the aminergic neurotransmitter serotonin (5-hydroxytryptamine, 5-HT), products of the kynurenine pathway of tryptophan metabolism (including 3-hydroxykynurenine, 3-hydroxyanthranilic acid, quinolinic acid and kynurenic acid), the neurohormone melatonin, several neuroactive kynuramine metabolites of melatonin, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
272
1
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(299 citation statements)
references
References 191 publications
3
272
1
13
Order By: Relevance
“…The majority of studies have found low tryptophan concentrations in serum (Widner et al 2000), plasma (Fekkes et al 1998) and CSF (Tohgi et al 1992) while other studies showed no alterations in tryptophan concentrations in plasma (Fonteh et al 2007) and brain (Storga et al 1996) in patients with AD. Low plasma tryptophan concentration might be also a consequence of the enhanced tryptophan degradation via the kynuramine pathway (Widner et al 2000), since a dysregulation of both serotonergic and kynuramine pathways of tryptophan metabolism have been associated with pathophysiology of AD (Ruddick et al 2006). In addition, the decline in the cognitive performance was observed after tryptophan depletion in healthy volunteers (Park et al 1994), patients with AD (Porter et al 2000) and patients with mild to moderate AD (Newhouse et al 2002), confirming the role of 5-HT system in behavioral and cognitive changes in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have found low tryptophan concentrations in serum (Widner et al 2000), plasma (Fekkes et al 1998) and CSF (Tohgi et al 1992) while other studies showed no alterations in tryptophan concentrations in plasma (Fonteh et al 2007) and brain (Storga et al 1996) in patients with AD. Low plasma tryptophan concentration might be also a consequence of the enhanced tryptophan degradation via the kynuramine pathway (Widner et al 2000), since a dysregulation of both serotonergic and kynuramine pathways of tryptophan metabolism have been associated with pathophysiology of AD (Ruddick et al 2006). In addition, the decline in the cognitive performance was observed after tryptophan depletion in healthy volunteers (Park et al 1994), patients with AD (Porter et al 2000) and patients with mild to moderate AD (Newhouse et al 2002), confirming the role of 5-HT system in behavioral and cognitive changes in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the kynurenine arm in the tryptophan metabolic pathway, which is observed in many disorders of the brain and the GI tract, 66 involves the catalytic enzyme indoleamine-2,3-dioxygenase, 40 the activity of which is induced by inflammatory mediators and by Clinical Therapeutics 962 Volume 37 Number 5 corticosteroids. 115 These findings suggest that alterations in the production of neuropeptides by dysbiosis would in turn alter the neuroendocrine-immune signaling or act directly on the CNS. The gut microbiota also impacts brain health in several ways.…”
Section: When Intimate Friends Turn Into Foesmentioning
confidence: 99%
“…Tryptophan is an essential amino acid for neurotransmitter serotonin (5-hydroxytryptamine, 5-HT) products. Impaired tryptophan metabolism has been implicated in the pathophysiology of conditions such as acquired immunodeficiency syndrome-related dementia, Huntington's disease and Alzheimer's disease [36]. The effect of MAAs on central signalling cascades has been investigated in human myelo monocytic THP-1 and THP-1-Blue cells [25].…”
Section: Maas and Gut-brain Axismentioning
confidence: 99%